Methodological Issues of Information Technology Research - Sauirbayeva Ә.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The article considers features of the system of mass communication and methodology of their research. Methods of research are interconnected with the path of development of information technologies and are innovative in relation to traditional means of mass communication. It is proposed to consider the media system taking into account the specifics of mobile, interactive and corporate communication. When researching information system technologies, it is necessary to take into account sufficiently communicative, political, social and psychological aspects of the content. This fact can be often observed in the writings of the Kazakh intellectuals. In the period of rapid development of the new media, it is necessary to master the diverse operational technology of journalism in collecting, preserving, processing information, as well as developing scientific approaches to the use of new technology and convergent journalism technology.